Biological mechanisms of resistance to trastuzumab and ways to overcome them: Mod-ern problems of clinical oncology - Vynnychenko, O.; Moskalenko, R. (Regulatory Mechanisms in Biosystems, 2024)
In 2022, 2.3 million new cases of breast cancer were registered in the world, which accounted for 11.6% of the total number of malignant neoplasms. Depending on the tumor’s molecular profile, the prognosis for patients can be different. One of the most aggressive types is HER2-positive breast cancer. Trastuzumab, a recombinant humanized monoclonal antibody against HER2, is used to treat such tumors. Congenital or acquired resistance to trastuzumab is one of the essential problems in clinical oncology. Our study aimed to investigate the resistance mechanisms to trastuzumab and ways to overcome them. This drug influences several directions of oncogenesis at the same time. The fundamental mechanisms of action of trastuzumab are inhibition of HER2 ectodomain shedding, inhibition of angiogenesis, degradation of HER2 protein and its internalization, inhibition of DNA repair, influence on the phosphatidylinositol 3-kinase pathway, cell cycle and antibody-dependent cellular cytotoxicity. The biological mechanisms of resistance to trastuzumab are based on vascular mimicry and hypoxia, the appearance of breast cancer stem cells, activation of alternative signaling pathways, metabolic changes, alternative molecular variants of HER2, changes in the processes of immune regulation, heterogeneity of expression and stability of the HER2 protein. In modern clinical oncology, trastuzumab is used as an original product and as antibody-drug conjugates. Trastuzumab emtansine and trastuzumab deruxtecan are approved for the treatment of patients with HER2-positive breast cancer, including those with low HER2 expression. This literature review identified the biological resistance mechanisms to trastuzumab and ways to overcome them. The implementation of new targeted drugs in combination with trastuzumab is the way to personalized treatment. It can significantly improve the survival of patients with HER2-positive breast cancer.